Differences in the pattern of evolution in six physically linked genes of Drosophila melanogaster - Zurovcová, Martina; Tatarenkov, Andrey; Berec, Ludek (Gene, 2006)
We describe DNA sequence polymorphisms at six loci (Acp26Aa, Acp26Ab, Acp29AB, Idgf1, Idgf3 and Ddc), all on the second chromosome of Drosophila melanogaster in one natural European population. Previous studies considering these loci separately showed that some of them were affected by natural selection. However, demographic processes or population admixture can produce footprints similar to natural selection. Simultaneous consideration of several genes may help to discern between selective and demography/admixture scenarios because the latter are expected to affect a majority of loci in a similar manner. Such an effect is not necessarily uniform among genes, but can be modified by rates of recombination and substitution. Since different evolutionary forces shaped the variation of the studied genes, our aim is to examine if their physical linkage could have affected the observed pattern. Fisher's conservative test of linkage disequilibrium is not significant. Lewontin's sign test pointed to linkage disequilibrium both within and between loci levels, though, none of the loci exhibits haplotype structure. Coupled with other results, the possibility of demography being the exclusive explanation for the observed variability is ruled out.
Keywords: rekombinace genetická; proteiny Drosophily; biologická evoluce; Recombination, Genetic; DNA; genetická variace; Selection, Genetic; Biological Evolution; Drosophila Proteins; polymorfismus genetický; Drosophila melanogaster; Linkage Disequilibrium; Genetic Variation; Polymorphism, Genetic; Gene Conversion; zvířata; mapování chromozomů; zeměpis; vazebná nerovnováha; genová konverze; Chromosome Mapping; selekce (genetika); Geography; Animals